2020
DOI: 10.1016/j.encep.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Les effets de confinement SARS-CoV-2 sur le sommeil : enquête en ligne au cours de la quatrième semaine de confinement

Abstract: Mots clés : Sommeil Confinement COVID 19 « Jet-lag » social Habitudes de sommeil r é s u m é Objectif.-Déterminer l'évolution du sommeil chez les Franç ais pendant le confinement motivé par la pandémie du SARS-CoV-2 et définir les facteurs comportementaux associés à un sommeil détérioré. Méthodologie.-Une enquête en ligne via les réseaux sociaux pendant la période de confinement. Les questions ont ciblé les conditions de confinement, les comportements relatifs au sommeil et les éléments de l'environnement pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
3
22
0
2
Order By: Relevance
“…We found a significant difference between men and women, which concurs with Hartley et al's [15] study but runs counter to Huang and Zhao's [23] preliminary publication. However, in Hartley et al's [15] findings, sleep-related factors were strongly associated with impaired sleep perception, with 90% of participants reporting shorter sleep, whereas in our survey the proportion of people for whom confinement resulted in an increase in sleep appears similar to the proportion of people for whom it resulted in a decrease, meaning that participants do not necessarily associate quality and quantity of sleep. During confinement, two things can decrease sleep pressure: a decrease in physical activity and an increase in anxiety that acts directly on the wakefulness systems [28].…”
Section: Impact Of Confinement On Sleepsupporting
confidence: 76%
“…We found a significant difference between men and women, which concurs with Hartley et al's [15] study but runs counter to Huang and Zhao's [23] preliminary publication. However, in Hartley et al's [15] findings, sleep-related factors were strongly associated with impaired sleep perception, with 90% of participants reporting shorter sleep, whereas in our survey the proportion of people for whom confinement resulted in an increase in sleep appears similar to the proportion of people for whom it resulted in a decrease, meaning that participants do not necessarily associate quality and quantity of sleep. During confinement, two things can decrease sleep pressure: a decrease in physical activity and an increase in anxiety that acts directly on the wakefulness systems [28].…”
Section: Impact Of Confinement On Sleepsupporting
confidence: 76%
“…However, this increase was similar to what was found in another study among Italian children and adolescents during the Covid-19 confinement ( 30 ); thus, this situation might have contributed to reinforcing timetables, which, in turn, might have been useful to mitigate potential detrimental effects over adequate sleep time ( 48 ). In contrast, a recent study among French adults found that 47% reported a decrease in sleep quality during quarantine, with sleep reduction being the most associated factor ( 49 ).…”
Section: Discussionmentioning
confidence: 93%
“…However, (48). In contrast, a recent study among French adults found that 47% reported a decrease in sleep quality during quarantine, with sleep reduction being the most associated factor (49).…”
Section: Sleep Timementioning
confidence: 92%
“…Changes in sleep habits and sleep disturbances were reported to be affected by COVID-19 [ 37 , 56 , 84 , 87 , 105 , 134 , 160 ]. Of note, some studies indicated that sleep issues were lower in older adults than in younger adults [ 122 , 134 , 147 ].…”
Section: Resultsmentioning
confidence: 99%